Management of Autonomic Dysfunction in Parkinson's Disease - Pfeiffer, Ronald F. (Seminars in Neurology, 2017)
Autonomic dysfunction is a frequent and important nonmotor feature of Parkinson's disease (PD). Autonomic dysfunction in PD spans a broad clinical spectrum. Cardiovascular dysfunction is characterized most prominently by orthostatic hypotension. Gastrointestinal dysfunction can involve virtually all levels of the gastrointestinal tract. Urinary dysfunction can entail either too frequent voiding or difficulty voiding. Sexual dysfunction is frequent and frustrating for both the patient and the partner. Alterations in sweating and body temperature are not widely recognized, but often are present. The presence of effective treatment for at least some aspects of autonomic dysfunction makes it vitally important that the assessment of autonomic dysfunction be a regular component of the neurologic history and examination for individuals with PD.
Keywords: autonomic; gastrointestinal; orthostatic hypotension; urinary; erectile dysfunction; thermoregulatory